Combining in-situ synchrotron X-ray microtomography and acoustic emission to characterize damage evolution in ceramic matrix composites. Issue 13 (October 2019) - Maillet, Emmanuel; Singhal, Anjali; Hilmas, Ashley; Gao, Yan; Zhou, Ying; Henson, Grant; Wilson, Gregory
Abstract: In-situ synchrotron X-ray microtomography and acoustic emission (AE) were combined to study the behavior of ceramic matrix composite laminates subjected to in-plane tensile or flexural loading at room temperature. A detailed characterization of the initiation and progression of two key damage modes (matrix cracking and fiber breaks) is obtained from microtomography, and the relationship between damage and AE is directly observed. A graphical representation of AE data, which has potential for real-time use, is employed to reveal differences in damage progression due to fiber architecture or loading mode. In addition, strong empirical relationships are observed between matrix crack area and AE energy, as well as between fiber breaks and number of AE events.